Despenalización del aborto consentido con base en la vulneración del derecho de la persona gestante, en el Ecuador, periodo 2020/2024. - Noboa Benavides, Naghely Lorena (2024)
In the present Titling Project was identified as the main object the decriminalization of consensual abortion in Ecuador, taking into consideration what is available the Constitution of the Republic, that started by collecting and theoretical analysis of the Ecuadorian legal normative and researches that precedes this project, the diagnosis through the sample, the subsequent explanation of the proposal and finished with the validation of the work, in front of the titling court. For it, a mixed focus was applied, compound by a qualitative part, to identify the reality of the subject and the study field, it means, from abortion and its decriminalization, and another quantitative for numerical and statistical values. The research methods: analytic-synthetic, inductive-deductive and historical-logical were chosen, that allow to identify chronologically the evolution to the abortion right, besides the defining the study object and identify the current situation of it inside the international and Ecuadorian legislation. Research technics were used such as the interview, the survey, applied to women from the Ibarra canton; quantity that was defined within a probabilistic, simple random sampling. Based on the informat ion, it was concluded that in Ecuador, women feel that their rights have been violated because it is prohibited the free and open access to self-induced abortion, forcing them to make it clandestinely, it is justified with various tools and international background, that in addition show the inefficiency of the legal normative that prohibits consensual abortions, and no considering the unborn fetus as a right subject, but the pregnant person.